2018
DOI: 10.1002/pon.4873
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of distress and quality of life in rare cancers

Abstract: Patients diagnosed with rare cancer reported poorer psychosocial outcomes and impaired quality of life when compared to the general population of cancer patients. Certain demographic groups (eg, women and younger patients) may benefit from targeted psychosocial interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 29 publications
6
22
0
8
Order By: Relevance
“…Although there is dearth of literature that documents the experiences of those living with PSC and their caregivers, many of the findings of this study are comparable to the experiences of those with other rare, serious or progressive illnesses. For instance, the presence of psychological distress is notable in those living with rare or advanced cancers [21,22]. Reduced physical…”
Section: Comparison To Previous Literaturementioning
confidence: 99%
“…Although there is dearth of literature that documents the experiences of those living with PSC and their caregivers, many of the findings of this study are comparable to the experiences of those with other rare, serious or progressive illnesses. For instance, the presence of psychological distress is notable in those living with rare or advanced cancers [21,22]. Reduced physical…”
Section: Comparison To Previous Literaturementioning
confidence: 99%
“…In addition, we report a case of severe anxiety associated with a rare cancer. Patients diagnosed with rare cancers report more severe anxiety than the general population of patients with cancer [6]. Our case did not respond to benzodiazepines, and it was difficult to use an SSRI as the next drug.…”
Section: Introductionmentioning
confidence: 57%
“…The prevalence of anxiety in patients with cancer is 10%-13% [1,2]. Patients diagnosed with rare cancers report more severe anxiety than the general population of patients with cancer [6].…”
Section: Discussionmentioning
confidence: 99%
“…A large proportion of patients reported moderate to severe distress, close to the one described among patients with metastatic cancer Mitchell et al, 2011) and higher than the one reported in a sample of Brazilian patients treated in private or public health care settings (Bergerot et al, 2016;Bergerot et al, 2017). This difference can be understood by the epidemiological characteristic of this disease (rare cancers), age group (young age is a risk factor), site of disease and treatment modalities (Acquati et al, 2018;Bergerot et al, 2018;Carpentier et al, 2011;Giese-Davis et al, 2012;Horick et al, 2017;Hoyt et al, 2013). But, also, by problems reported by these patients (e.g., pain, fatigue, worry and financial problems), suggesting a similar relevance to patients undergoing treatment, which requires extended psychosocial support (Jacobsen, Nipp, & Ganz, 2017).…”
Section: Discussionmentioning
confidence: 88%